2014
DOI: 10.1371/journal.pone.0113720
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Co-Infection with Multiple Torque Teno Sus Virus Species in Italian Pig Herds

Abstract: Torque teno viruses (TTVs) are a large group of vertebrate-infecting small viruses with circular single-stranded DNA, classified in the Anelloviridae family. In swine, two genetically distinct species, Torque teno sus virus 1a (TTSuV1a) and 1b (TTSuV1b) are currently grouped into the genus Iotatorquevirus. More recently, a novel Torque teno sus virus species, named Torque teno sus virus k2b (TTSuVk2b), has been included with Torque teno sus virus k2a (TTSuVk2a) into the genus Kappatorquevirus. In the present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 36 publications
2
13
1
Order By: Relevance
“…Data related to infection with TTSuVk2b, the most recently identified species, are still limited. A study on 244 pig serum samples from 17 different countries reported an overall 40% prevalence of infection [36], whereas Blois et al reported an 11.5% prevalence of TTSuVk2b in 721 Italian pigs [70]. The high prevalence of TTSuV in the swine population indicates the existence of effective mechanisms of transmission.…”
Section: Animal Ttvsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data related to infection with TTSuVk2b, the most recently identified species, are still limited. A study on 244 pig serum samples from 17 different countries reported an overall 40% prevalence of infection [36], whereas Blois et al reported an 11.5% prevalence of TTSuVk2b in 721 Italian pigs [70]. The high prevalence of TTSuV in the swine population indicates the existence of effective mechanisms of transmission.…”
Section: Animal Ttvsmentioning
confidence: 99%
“…Regarding AVs infecting animals, most studies to date have focused on the role of TTSuV in pig diseases. Although TTSuVs were found at particularly high frequency in healthy animals [70,72], they are currently receiving more attention due to the latest results on disease association. In fact, TTSuVs are considered non-pathogenic by themselves, but there is increasing evidence that points to their influence on the development of some diseases or suggests that these viruses even affect disease outcome [66].…”
Section: Innocent Bystanders or Something Else?mentioning
confidence: 99%
“…TTSuVs possess a single‐stranded, circular DNA genome (Meng, ). Porcine TTSuVs have been classified into two genera, genus Iotatorquevirus (TTSuV1, species TTSuV1a and TTSuV1b) and genus Kappatorquevirus (TTSuVk2a, and the more recently reported novel TTSuV species, TTSuVk2b) (Blois et al., ; Cornelissen‐Keijsers et al., ; Kekarainen & Segalés, ; Rogers et al., ). TTSuV DNA has been found in various porcine tissues including brain, bone marrow, heart, liver, lungs, lymph nodes, kidneys and spleen, indicating a tropism for multiple tissues (Aramouni, Segalés, Cortey, & Kekarainen, ; Kekarainen & Segalés, ; Meng, ; Monini et al., ; Nieto, Kekarainen, Aramouni, & Segalés, ).…”
Section: Introductionmentioning
confidence: 99%
“…High prevalence rates of TTSuV1 and TTSuVk2a including co‐infection with these viruses species have been reported in both diseased and apparently healthy pigs from different parts of the world (Blois et al., ; Kekarainen & Segalés, ; Meng, ). Although the pathogenicity of TTSuV remains to be clearly elucidated, it is possible that TTSuVs may act as a cofactor, or trigger the development of disease caused by other porcine pathogens (Kekarainen & Segalés, ; Meng, ; Rogers et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation